1992
DOI: 10.1002/bbpc.19920960350
|View full text |Cite
|
Sign up to set email alerts
|

Atmospheric Reactions in Cryogenic Matrices: Photooxidation of Carbonyl Sulfide (SCO) by Ozone

Abstract: Photooxidation of carbonyl sulfide (SCO) in the presence of ozone has been studied in solid matrices under stratospheric irradiation conditions. The matrix experiments allowed the isolation and identification of SCO ' 0 , 1 : 1 aggregates. Selective photolysis of O3 yielded O('D) atoms and subsequent reaction with SCO resulted in the primary formation of C 0 2 + S. The sulfur atoms generated this way are oxidized to SO? by 02, which has been formed during photofragmentation of 03. In further steps SO2 reacted … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
6
0

Year Published

2003
2003
2013
2013

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 22 publications
1
6
0
Order By: Relevance
“…In contrast, Jaeger et al performed similar matrix experiments and reported that reaction 5 is major; some S atom product is further oxidized to SO 2 , SO 3 , and SO 4 . 16 Their 18 O 3 / 16 OCS experiments lead to the formation of S 18 O 2 and 16 OC 18 O, supporting the proposed mechanism. To investigate the gaseous reaction of O( 1 D) + OCS, Shortridge and Lin applied resonance absorption of CO laser emission to determine the vibrational population of CO produced upon UV (λ > 215 nm) photolysis of mixtures of O 3 /OCS/SF 6 ; CO (V e 9) with vibrational temperature of 3300 K, corresponding to 4% of the available reaction energy, was reported.…”
Section: Introductionsupporting
confidence: 69%
“…In contrast, Jaeger et al performed similar matrix experiments and reported that reaction 5 is major; some S atom product is further oxidized to SO 2 , SO 3 , and SO 4 . 16 Their 18 O 3 / 16 OCS experiments lead to the formation of S 18 O 2 and 16 OC 18 O, supporting the proposed mechanism. To investigate the gaseous reaction of O( 1 D) + OCS, Shortridge and Lin applied resonance absorption of CO laser emission to determine the vibrational population of CO produced upon UV (λ > 215 nm) photolysis of mixtures of O 3 /OCS/SF 6 ; CO (V e 9) with vibrational temperature of 3300 K, corresponding to 4% of the available reaction energy, was reported.…”
Section: Introductionsupporting
confidence: 69%
“…Syntheses to this end had been performed in the past for studying many natural and other phenomena associated with SO 2 . Such molecules were obtained by burning sulfur in the environment of expensive 18 O 2 18 (made from H 2 18 O), difficult to control mixtures of 16 O 2 and 18 O 2 , or with the hard to get 18 O 3 . The present reaction offers a direct way for making S 18 O 2 , S 16 O 18 O, and other variations simply by heating slightly the thermally unstable episulfones which decompose to SO 2 and the corresponding olefin.…”
mentioning
confidence: 97%
“…17 Such molecules were obtained by burning sulfur in the environment of expensive 18 O 2 18 (made from H 2 18 O), difficult to control mixtures of 16 O 2 and 18 O 2 , 19 or with the hard to get 18 O 3 . 20 The present reaction offers a direct way for making S 18 O 2 , S 16 In conclusion, HOF‚CH 3 CN made readily from F 2 is a powerful and versatile tool in general chemistry whenever (15) Fialkov, A. B.; Amirav, A. J.…”
mentioning
confidence: 97%
“…There has been only one report on the rate coefficient indirectly determined using a reference reaction O( 1 D) + O 2 ? O ( 3 P) + O 2 [12], although a few studies on the reaction products have been reported [6,[13][14][15]. Chiang et al [15] have recently observed infrared emission from CO and CO 2 in the O 3 /OCS/Ar/248 nm system using time-resolved Fourier-transform infrared spectroscopy, giving evidence for direct generation of CO and CO 2 in the reaction O( 1 D) + OCS.…”
Section: Introductionmentioning
confidence: 97%